Modified SERVPERF and Normalized SERVQUAL Models in Estimation of Service Quality in Higher Educational Institutes - Sydorov, Mykola; Salnikova, Svitlana; Savelyev, Yuriy; Oliinyk, Oksana; Сидоров, Микола; Сальнікова, Світлана; Савельєв, Юрій; Олійник, Оксана; Сидоров, Николай; Сальникова, Светлана; Савельев, Юрий; Олейник, Оксана (Східноєвропейський національний університет імені Лесі Українки, 2020)
The purpose of this paper is to propose and empirically substantiate modification of SERVPERF instrument. We demonstrate difference in practical realization of SERVQUAL (Perceptions-Minus-Expectations) and modified SERVPERF (Performance-Minus-Expectation) based on qualitative and two quantitative methodological studies carried out at the Faculty of Sociology of Taras Shevchenko National University of Kyiv. We used questionnaire adaptation for higher educational institutes (HEI).The sample size of the quantitative studies (10 persons of 2nd year of education, 10 persons of 3nd year of education, 10 persons of 4th year of Bachelor degree program and 5 persons of 2nd year of Master degree program; every 4th student of each year of education) complies with the used statistical test and the sample size requirements for focus groups. To compare the instruments we used nonparametric Wilcoxon signed rank test implemented in the statistical programming package R. Our finding is that modified SERVPERF is more convenient for students, smaller and more useful for online surveys. So, the difference in mean values of answer’s levels is more significant between modified SERVPERF and normalized SERVQUAL than between modified SERVPERF and perceptions in SERVQUAL. Although the research has limitation – it is reconnaissance one and made as a one of steps for adaptation and validation of models for service quality measuring in Ukrainian HEI based on survey of Taras Shevchenko National University of Kyiv students, however, the results of this methodological study allow other researchers to conduct representative studies using an adapted questionnaire of SERVQUAL at their universities. This result is important for service quality estimation which is needed for universities to monitor and improve the quality of their services and elaborate marketing strategy now.

Мета роботи – запропонувати та емпірично обґрунтувати модифікацію інструменту SERVPERF. Продемонстровано відмінності в практичній реалізації SERVQUAL і модифікованого SERVPERF на основі якісних та двох кількісних методологічних досліджень, проведених на факультеті соціології Київського національного університету імені Тараса Шевченка. Застосовано адаптацію анкети для вищих закладів освіти (ВЗО). Для порівняння інструментів використано непараметричний тест рангового підписання Вілкоксоном, реалізований у пакеті статистичного програмування R. Висновок полягає в тому, що модифікований SERVPERF є більш зручним для студентів, меншим і кориснішим для онлайн-опитувань. Такий результат важливий для оцінки якості послуг, яка потрібна університетам для моніторингу та покращення якості своїх послуг і розробки маркетингової стратегії.

Цель работы – подтверждение различий в практической реализации двух подходов SERVQUAL и модифицированного SERVPERF, а также обоснование выбора на основе пилотного исследования студентов вузов. Для этого проводятся два пилотных опроса с использованием SERVQUAL (восприятие–минус–ожидания) и модифицированных подходов SERVPERF (представление–минус–ожидание) среди студентов факультета социологии (по 10 студентов 2–4 годов обучения на бакалаврате и пяти человек 2 курса магистратуры) по адаптированной анкете. Для сравнения средних значений каждого компонента проводился парный t-критерий, а затем – качественное интервью со всеми респондентами об удобстве двух анкет, четкости основных вопросов и т. д. По итогам исследования, модифицированный SERVPERF является более удобным для студентов, и полезнее для онлайн-опросов.
Модифіковані SERVPERF і нормалізовані моделі SERVQUAL в оцінці якості обслуговування у вищому закладі освіти
Модифицированные SERVPERF и нормализованные модели SERVQUAL в оценке качества обслуживания в вузе
Keywords: HEI; quality of education; sociological research; SERVPERF; SERVQUAL; вищий заклад освіти; якість освіти; соціологічне дослідження; 316